The effects of a mindfulness-based program on higher education students - Serrão, Carla; Rodrigues, Ana Rita; Ferreira, Tiago (Frontiers in Education, 2022)
Background Entering higher education is a process with multiple challenges that requires the mobilization of personal, social and instrumental resources. As a result, students tend to experience grater stress, anxiety, and depression. In this regard, mindfulness-based interventions (MBIs) can serve as a useful tool to help students deal with these demands. Objective This study aimed to evaluate the effect of a Mindfulness in Education program in reducing stress, anxiety, and depression symptoms among students. Methods Forty-four students of higher education from four degrees in the fields of Social and Cultural Sciences participated and finished surveys before and after the 12-weeks intervention, measuring stress, depression, anxiety, mindfulness, and self-compassion. Twenty-three students (82.61% female; Mage = 20.35 DPage = 3.24) participated in Mindfulness in Education. These participants were paired with 21 students (90.48% female; Mage = 18.67, DPage = 0.73), which constituted the control condition. Results The results showed a session × condition interaction that was statistically significant for depression (p < 0.012) and stress (p < 0.026). In the follow-up exploration, the experimental condition revealed a statistically significant and moderate change in the severity of the symptoms of depression [t(14) = –2.315, p = 0.036, ξ = 0.304, 95% CI (–0.023, –0.499)] but not at the stress level [t(14) = –1.443, p = 0.171, ξ = 0.223, 95% CI (–0.006, –0.364)]. Conclusion Outcomes were promising, adding to evidence that MBIs can play an important role in helping students manage stress and depression. However, it is still necessary to investigate the mechanisms underlying this type of interventions.